The Research on Supply Chain Management in Outsourcing Process: A Case Study of Apple Inc. - ZHAO, WEIQI (2016)
Abstract: With the development of economic globalization, outsourcing is becoming a more and more popular model for enterprises all over the world. This article will discuss the driving factors behind the outsourcing strategy and also illustrate the potential risk in supply chain in outsourcing process. By concentrating on the supply chain management in outsourcing process and using case study of Apple Inc. and comparing with Samsung Electronics, this article try to analysis how to operate outsourcing strategy and get good outcome. Try to use the result of analysis to find the way of how to control the risk to a minimum level in supply chain operation and the room for promotion for Apple.